Klara and the sun - Ishiguro, Kazuo, 1954- (London, England ; India : Faber & Faber ; Replika Press, 2022)
*The #1 Sunday Times Bestseller* *Longlisted for the Booker Prize 2021* *A Barack Obama Summer Reading Pick* 'A delicate, haunting story' The Washington Post 'This is a novel for fans of Never Let Me Go . . . tender, touching and true.' The Times 'The Sun always has ways to reach us.' From her place in the store, Klara, an Artificial Friend with outstanding observational qualities, watches carefully the behaviour of those who come in to browse, and of those who pass in the street outside. She remains hopeful a customer will soon choose her, but when the possibility emerges that her circumstances may change for ever, Klara is warned not to invest too much in the promises of humans. In Klara and The Sun, Kazuo Ishiguro looks at our rapidly changing world through the eyes of an unforgettable narrator to explore a fundamental question: what does it mean to love? Kazuo Ishiguro's book Klara and the Sun was a #1 Sunday Times Bestseller w/c 06-03-2021
First published in 2021.
Keywords: Future, The -- Fiction; Artificial intelligence -- Fiction; Robots -- Fiction; Science fiction; Love stories